Pengaruh Penggantian Bahan Pengisi Semen Dengan Kombinasi Abu Bata Dan Abu Sekam Padi Pada Campuran Aspal AC-BC - Ahmad Fajriman; Alfian Malik; Gunawan Wibisono (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Portland cement is usually used in asphalt concrete as filler. Brick ash and rice husk have similar chemical compound to portland cement. This research tried to utilize a combination of those ashes to replace cement. The purpose of this research is to determine the Marshall characteristics of asphalt concrete binder course (AC-BC) mixtures using the mixed ash as filler. The mixed of ash contained 40% brick ash and 60% rice husk ash. Ratios of cement and the mixed ash were 100:0, 50:50, 0:100. All samples were made and tested according to Bina Marga 2010 Revision 3 Specification. Based on Marshall characteristics, the addition of brick and rice husk ash increased stability and void filled asphalt (VFA) values, and reduced the air void. Keywords: Rice husk ash, Brick ash, Filler, Asphalt concrete binder course